Efficacy of a new dual channel laryngeal mask airway, the LMA®Gastro™ Airway, for upper gastrointestinal endoscopy: a prospective observational study. (February 2018) - Terblanche, N.C.S.; Middleton, C.; Choi-Lundberg, D.L.; Skinner, M.
Abstract: Background: Significant cardiorespiratory events are frequent in patients undergoing gastrointestinal endoscopy. Central to the occurrence of respiratory events is an unsecured airway. This study sought to determine the efficacy of a new laryngeal mask airway, the LMA ® Gastro TM Airway (Teleflex Medical, Athlone, Ireland), in patients undergoing upper gastrointestinal endoscopy. New design features include a dedicated channel for oesophageal intubation and separate channel with terminal cuff for lung ventilation. Methods: In a prospective, open label, observational study, 292 ASA physical status classification 1 and 2 patients at low risk of pulmonary aspiration undergoing upper gastrointestinal endoscopy received i.v. propofol anaesthesia and standardized insertion of the LMA ® Gastro TM Airway. Endoscopy outcomes included insertion success, first attempt success, and ease of endoscope insertion. LMA ® Gastro TM Airway outcomes included insertion success, first attempt success, ease of insertion, lowest oxygen saturation, airway compromise, laryngospasm, bloodstained device, and sore throat. Results: Per protocol analysis ( n =290), the endoscopy success rate amongst the cohort with successful LMA ® Gastro TM Airway insertion was 99% [95% confidence interval (CI): 98, 100]. LMA ® Gastro TM Airway insertion success rate ( n =292) was 99% (95% CI: 98, 100). For endoscopy and LMA ® Gastro TM Airway insertion success, the lower limit of the 95% CIs was at least 98%, indicating LMA ® Gastro TM Airway efficacy. Median (inter-quartile range) lowest intraoperative oxygen saturation was 98% (98, 99). Only one serious adverse event occurred (re-admission for sore throat and inability to tolerate fluids) and was reported to the Tasmanian Health and Medical Human Research Ethics Committee. Conclusions: The LMA ® Gastro TM Airway appears effective for clinical use in upper gastrointestinal endoscopy. Clinical trial registration: ACTRN12616001464459.